Do non-profit sport organisations innovate? Types and preferences of service innovation within regional sport federations. Issue 3 (2nd July 2016) - Winand, Mathieu; Scheerder, Jeroen; Vos, Steven; Zintz, Thierry
Abstract : Little is known about innovation in the non-profit sport sector. The current research addresses this gap by questioning whether and to what extent sport federations innovate. It aims to identify types of innovation implemented by sport federations and their attitude and preferences towards innovation. An online questionnaire was administered to a sample of key representatives (i.e. Chair, Secretary General or Directors) of regional sport federations in Belgium ( n = 101; 70% response rate). Directed content analysis of the service innovations described by respondents reveals ten different types of sport and non-sport service innovations. Results suggest that membership size and categories of sport influence preferences in knowledge creation/appropriation, and ultimately the type of innovation developed. This paper also suggests that sport federations are driven by demands by members in meeting their expectations of new services and are not risk averse. On average, the sport federations surveyed have a positive attitude towards newness that favours innovativeness. The current study would help researchers to advance further into the knowledge of service innovation in non-profit organisations. It should act as a foundation for research and practice on specific types of service innovation in sport. Managers should realise the importance of attitude for innovation and use the suggested typology to provide new services in different categories and meet members' expectations.